IDENTIFIKASI POLA DAN EFISIENSI TATA NIAGA ROTAN DI JAWA - Achmad Supriadi; Osly Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
The marketing chain of rattan commodity is closely related to the income distribution of those who perform efficiently the marketing and mechanism system of rattan. This study deals with the investigation on the patterns of rattan-marketing in Java, i.e. (I) Inter-islands merchant –> rattan crafter –> crafter collector –> domestic consumer; (2) Inter-islands merchant –> rattan crafter –> domestic consumer; (3) Rattan crafter –> exporter producer –> overseas consumer.Viewed from the degree of benefit, all the parties involved in those rattan-marketings have gained a reasonable benefit with the revenue and cost ratio (RCR) values ranging between 1.11 and 1.27. Evaluated from the benefit distribution, rattan marketing with pattern (1) was efficient, while those with pattern (2) and (3) were inefficient and the most efficient, respectively. In the pattern (3). there appeared a positive trend about the presence of domination by Exporter producer. This is be cause that domination has brought about some benefit to those taking part in the other rattan-marketing activities. Keywords : Rattan, marketing, efficiency, and benefit.